Reaction of rubber tree clones to various isolates of Microcyclus ulei - Junqueira, Nilton T. V.; Chaves, Geraldo M.; Zambolim, Laércio; Alfenas, Acelino C.; Gasparotto, Luadir (Pesquisa Agropecuaria Brasileira, 2014)
The reactions of 33 clones of Hevea to various M. ulei isolates collected from rubber plantations in different regions of Brazil were studied. Isolates were inoculated with a concentration of 2 x 105 conidia/ml with 70% - 80% of germination rate. The subculturing was made with a 12-day old culture macerated in distilled sterilized water. The reaction presented by clones of Hevea spp varied with isolates and with clones. Most of the clones showed complete resistance to some of the isolates, but the same clones were susceptible or highly susceptible to the others. Some clones showed complete resistance and varying levels of incomplete resistance. It was verified that both the latent period and the diameter of lesions may be related to rubber tree resistance to M. ulei, but these two parameters are not sufficient to explain this resistance. The association of various resistance components is needed. Among these components, the "sporulation on the lesions" is the most important. The incubation period and number of lesions are not good parameters for analyzing the rubber tree resistance to M. ulei.
Keywords: Hevea spp; leaf blight; incomplete resistance; complete resistance